High Resolution Direction of Arrival Estimation with Switched Active Switched Parasitic Antenna Arrays - Jasem, Rabah Abduljabbar (Curtin University, 2020)
This thesis investigates the ability of Switched Active Switched Parasitic antenna (SASPA) as direction finding arrays. SASPA array consists of N identical antennas in which one element is in active state while the others are parasites during one point of measurement time. The improvements in direction of arrival estimation achieved by using SASPA arrays were examined under different scenarios of the data model. Several estimations were conducted to depict the outperformance of SASPA arrays over all-active antenna arrays.